Mothering, Migration and the Global Village: Understanding Support for Mothering in the 21st Century Caribbean - Sherma Foster, Juliana (Journal of the Motherhood Initiative for Research and Community Involvement, 2013)
This paper discusses some of the key findings from an exploratory study of Caribbean migrant mothers in Trinidad and Tobago and the role of the global media and web resources in supporting them as twenty-first century mothers. Social Capital theory was applied for assessing the importance of parental support networks for migrant mothers. The methodology employed included analysis of secondary data such as parenting web sites. Migrant mothers interviewed were identified through the snowball sampling method and questioned on their sources of support in their new home. The study reveals that post-modern Caribbean families are greatly affected by migration. Support networks are part of a mother’s social capital and many benefits are derived from those networks, whether local, trans-national, multi-national or virtual. Though these networks may be weakened through migration, information and telecommunications technology are of key importance in facilitating the maintenance of old and the building of new support networks. The role of the “village” in providing support remains significant. However, the village in the twenty-first century can now be conceptualized as ‘real’ or virtual’ spaces.